A robust and tunable halogen bond organocatalyzed 2-deoxyglycosylation involving quantum tunneling - Xu, Chunfa (Nat Commun, 2020)
The development of noncovalent halogen bonding (XB) catalysis is rapidly gaining traction, as isolated reports documented better performance than the well-established hydrogen bonding thiourea catalysis. However, convincing cases allowing XB activation to be competitive in challenging bond formations are lacking. Herein, we report a robust XB catalyzed 2-deoxyglycosylation, featuring a biomimetic reaction network indicative of dynamic XB activation. Benchmarking studies uncovered an improved substrate tolerance compared to thiourea-catalyzed protocols. Kinetic investigations reveal an autoinductive sigmoidal kinetic profile, supporting an in situ amplification of a XB dependent active catalytic species. Kinetic isotopic effect measurements further support quantum tunneling in the rate determining step. Furthermore, we demonstrate XB catalysis tunability via a halogen swapping strategy, facilitating 2-deoxyribosylations of D-ribals. This protocol showcases the clear emergence of XB catalysis as a versatile activation mode in noncovalent organocatalysis, and as an important addition to the catalytic toolbox of chemical glycosylations.